Қарақалпақстанда этноспорт ҳәм миллий балалар ойынларын изертлеўдиң дәслепки көринислери - Елмуратов, Ч (SCIENCE and SOCIETY, 2023)
The scientific article is devoted ethnosport and national children's games of Karakalpak, and learns about the research works and scientific achievements of scientists who have been conducting research since the 19th century. In particular, the views of world-renowned scientists and ethnographers on Karakalpak national games of children and young adults, the issues of research and presentation of national games by local scientists and organizers were discussed in the press.
Keywords: ethnic sports; folk games of Karakalpak; outdoor games; children and teenagers